EDUCATION OF THE IMPACT OF SMARTPHONE USE ON SPEAKING AND LANGUAGE ABILITIES IN EARLY CHILDHOOD IN KHADIJAH KINDERGARTEN 201, BANYUWANGI REGENCY: EDUCATION OF THE IMPACT OF SMARTPHONE USE ON SPEAKING AND LANGUAGE ABILITIES IN EARLY CHILDHOOD IN KHADIJAH KINDERGARTEN 201, BANYUWANGI REGENCY - nofitasari, intan (Fetus : Journal of Midwifery, 2024)
Abstract The use of smartphones in various fields means that smartphones are used by various groups, including children. In fact, quite a few parents introduce smartphones to their children under five years old with the excuse of "bribing" their children not to be fussy. This will affect their development, especially language development in early childhood. The aim of this research is to determine the effect of smartphone use on language development in children. This activity is carried out by providing counseling to parents/guardians of children aged 4-6 years. This counseling was carried out at Khadijah Kindergarten 201 which was attended by 44 parents. The results of the counseling were obtained. Before the counseling was given, 18 participants (51%) had good knowledge and after the activity there was an increase to 30 participants (86%) with good knowledge. Parents are very enthusiastic and active in receiving material and taking part in activities to minimize the influence of smartphone use on children's language development.